A modal account of propositions. (29th January 2018) - Yu, Andy Demfree
Abstract: In this paper, I motivate a modal account of propositions on the basis of an iterative conception of propositions. As an application, I suggest that the account provides a satisfying solution to (a version of) the Russell‐Myhill paradox. The account is in the spirit of recently developed modal accounts of sets motivated on the basis of the iterative conception of sets.